2011
DOI: 10.1371/journal.pone.0028775
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic Diversity of African Tigerfish (Genus Hydrocynus) Reveals Palaeogeographic Signatures of Linked Neogene Geotectonic Events

Abstract: The geobiotic history of landscapes can exhibit controls by tectonics over biotic evolution. This causal relationship positions ecologically specialized species as biotic indicators to decipher details of landscape evolution. Phylogeographic statistics that reconstruct spatio-temporal details of evolutionary histories of aquatic species, including fishes, can reveal key events of drainage evolution, notably where geochronological resolution is insufficient. Where geochronological resolution is insufficient, ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
81
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(94 citation statements)
references
References 84 publications
13
81
0
Order By: Relevance
“…Molecular techniques like DNA barcoding have already proven to be powerful for the identification of both marine and freshwater fish taxa Pereira et al 2013), and to detect cryptic species diversity or taxonomic inconsistencies (Goodier et al 2011;Collins & Cruickshank 2012;Decru et al 2016). However, the uncritical use of molecular tools to identify species, especially using only a single molecular locus (mt genome), is unwarranted (DeSalle et al 2011), and traditional morphology has proven its value as a suitable technique to assess the diversity in many taxa.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular techniques like DNA barcoding have already proven to be powerful for the identification of both marine and freshwater fish taxa Pereira et al 2013), and to detect cryptic species diversity or taxonomic inconsistencies (Goodier et al 2011;Collins & Cruickshank 2012;Decru et al 2016). However, the uncritical use of molecular tools to identify species, especially using only a single molecular locus (mt genome), is unwarranted (DeSalle et al 2011), and traditional morphology has proven its value as a suitable technique to assess the diversity in many taxa.…”
Section: Introductionmentioning
confidence: 99%
“…Construction of spatio-temporal details of the evolutionary histories of fishes can reveal key events of drainage evolution Goodier et al 2011). This is because the biogeography of extant freshwater fishes represents responses to landscape evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the evolutionary history of each aquatic species is characterized by a distinct pattern of genetic variation, which includes persisting relics of drainage evolution (Craw et al 2007). Goodier et al (2011) studied the phylogeography of the African tigerfish of the genus Hydrocynus and found that the diversity and distribution of Hydrocynus reflect a complex history of vicariance and dispersal. Moreover, range expansions in this particular species testify to changes in drainage basins, and the principal divergence events in Hydrocynus have closely interfaced with evolving drainage systems across tropical Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a cytochrome b gene study (Goodier et al 2011) suggested possible cryptic diversity in the species, with possibly five separate species in the Congo basin. Although no samples of H. vittatus from the Nile basin were included in their analyses, their results highlight the need of a taxonomic revision and the possibility of detecting additional species in areas outside their study region.…”
Section: Examination Of Congo-albertine Rift Ich-thyofaunal Similaritiesmentioning
confidence: 99%